BS EN IEC 61753-051-02. Fibre optic interconnecting devices and passive components. Performance standard. Part 051-02. Plug-receptacle style single-mode fibre fixed optical attenuators for category C. Controlled environments (23rd October 2020) - British Standards Institution,
No abstract available